Cinacalcet inhibition of neuronal action potentials preferentially targets the fast inactivated state of voltage-gated sodium channels - Lindner, Jamie S.; Rajayer, Salil R.; Martiszus, Briana J.; Smith, Stephen M. (Frontiers in Physiology, 2022)
Voltage-gated sodium channel (VGSC) activation is essential for action potential generation in the brain. Allosteric calcium-sensing receptor (CaSR) agonist, cinacalcet, strongly and ubiquitously inhibits VGSC currents in neocortical neurons via an unidentified, G-protein-dependent inhibitory molecule. Here, using whole-cell patch clamp methods, we investigated the voltage-dependence of cinacalcet-mediated inhibition of VGSCs and the channel state preference of cinacalcet. The rate of inhibition of VGSC currents was accelerated at more depolarized holding potentials. Cinacalcet shifted the voltage-dependence of both fast and slow inactivation of VGSC currents in the hyperpolarizing direction. Utilizing a simple model, the voltage-dependence of VGSC current inhibition may be explained if the affinity of the inhibitory molecule to the channel states follows the sequence: fast-inactivated > slow-inactivated > resting. The state dependence of VGSC current inhibition contributes to the non-linearity of action potential block by cinacalcet. This dynamic and abundant signaling pathway by which cinacalcet regulates VGSC currents provides an important voltage-dependent mechanism for modulating central neuronal excitability.